Avaliação da infecção do líquido ascítico em pacientes cirróticos e seu perfil de resistência bacteriana - Bruno Campos Santos (2024)
Bacterial infection is responsible for about 44% of decompensated liver cirrhosis, and spontaneous bacterial peritonitis (SPB) is a major cause of infection in this group. Empirical antibiotic therapy should be promptly started for better outcomes. Recent changes in microbiology are challenging adequate antimicrobial regimen. An increase in the prevalence of gram-positive and multi-drug resistant bacteria in ascitic fluid samples of patients with SBP has been recently described. Those changes are not homogenous worldwide, so international societies suggest frequent assessments of local microbiology. This study aimed to evaluate the prevalence of SBP in ascitic fluid of cirrhotic inpatients at the HC-UFMG, as well as local microbiological profile and resistance pattern. Methods: A retrospective study assessed data of 366 adults who underwent abdominal paracentesis between 01/01/2017 and 09/13/2021 in a quaternary hospital. Collected data included demographic characteristics; etiology of cirrhosis; ascitic fluid characteristics; presence of SBP, bacterascites or absence of infection; microbiological profile and resistance pattern; prophylaxis; empirical treatment and outcomes. Results: A total of 121 cases of SBP and 14 cases of bacterascites were registered in 366 patients during the period of the study. Alcohol-associated liver disease was the main cause of cirrhosis (43,7%), followed by viral hepatitis (24,8%). Bacterial growth was noted in 32 samples with SBP and in 14 bacterascites samples. Escherichia coli was the main isolated bacteria (n = 20), and Gram-negative microorganisms were responsible for 62% of the cases. Only 50% of the samples were considered susceptible to most drugs, and 10% of the remaining were considered extensively drug resistant bacteria. Of the tested bacteria, 48% were resistant to ceftriaxone, 46% to ciprofloxacin, 33% to piperacillin + tazobactam and 21% to meropenem. There was an association between healthcare related and hospital acquired infections and higher rates of in vitro drug resistance when compared do community acquired infections (p = 0,046). This study found no statistical relevant association between drug resistant and poorer outcomes or longer hospital stays. Conclusion: This study found a significant presence of antibiotic resistance in SBP and bacterascites among cirrhotic patients. Resistance to key antibiotics like ceftriaxone underscores the need for precise antimicrobial strategies, emphasizing the importance of local resistance patterns. Incorporating patients' healthcare history into the decision-making process can enhance the precision in choosing antimicrobials, suggesting a path towards more individualized patient care.